Content validity of gymnastics through movement and song programmes and its impacts on kindergarten students’ balance - Pradipta, Galih Dwi; Rachmawati, Umi (UIR Press, 2025)
Background: Gymnastics learning is considered an exercise programme that is aimed at improving the balance movement skills of kindergarten students. There is a limited gymnastic program to develop the kindergarten students’ balance and movement skills that meet the students’ needs and wants. Research Objectives: The purpose of this study is to determine the feasibility of gymnastics learning activities on the ability to move balance for kindergarten students. Methods: This research is an R&D, a movement and song gymnastics program for the kindergarten students’ balance. The participants involve 30 students aged 5-6 years. The validators were five experts focusing on the topic addressed. The first stage examines qualitatively articles, e-books, textbooks, and programme design. The second stage applies the Aiken’s V technique to assess the training program. The third stage analyses the assessment results. The fourth stage tests the training programme. Findings and Results: Based on the results of Aiken V’s analysis related to the movement and song gymnastics program developed, the overall score shows a range of 0.8 to 1.00. The programme is feasible and valid as a balance movement learning in kindergarten. Conclusion: The movement and song practice programs that have been prepared have good and valid content validity. The novelty of this study is to develop a gymnastics program integrated with the educational curriculum for kindergarten children. This includes designing activities taking into account the differences in each child's level of balance, strength, and motor skills. The programme will be applied to students to know the effectiveness of the movement and song training program for gymnastics on the balance ability of kindergarten students.